Militarisation of COVID-19 responses and autocratisation: a comparative study of eight countries in Asia-Pacific and Latin America - Croissant, Aurel; Kühn, David; Macias-Weller, Ariam; Pion-Berlin, David (The Journal of East Asian affairs, 2023)
This working paper examines the military’s contributions to COVID-19 pandemic responses and their implications for democracy in eight countries in in Asia-Pacific and Latin America.
Gesehen am 04.07.2024